Fostering Productive Village Youth: Soft-Skills and Work Culture Development through Village-Owned Enterprise (BUMDes) Programs in Cibrek Baroh Village - Pratama, M. Fikri Jaka; Maszura, Leni; Lestari, Maya; Safitri, Yulia Nanda; Rahma, Febriani; Iramadhani, Dwi; Akbar, Muhammad Naufal; Tambun, Vincent (Yayasan Mata Pena Madani, 2025)
Village youth have great potential in community development as they are in a phase of character building, skill development, and work ethic formation. However, in Gampong Cibrek Baroh, this potential has not been fully optimized due to low education levels, limited training opportunities, and a lack of self-development spaces. The Village-Owned Enterprise (BUMDes) is expected to serve as a platform for youth empowerment, yet it still focuses mainly on asset management without addressing human resource development. This situation results in low participation and readiness among youth in village economic activities, as well as increasing dependence on parents. Through a community service program in the form of soft-skill training and the establishment of a productive work culture integrated with BUMDes activities, it is hoped that the capacity of youth as local development actors can be strengthened. The results of the program indicate improved awareness, participation, and collaborative spirit among youth. Quantitatively, the average pre-test score of 72.75 increased to 88.50 on the post-test, showing a general and more evenly distributed improvement in participants’ abilities. In addition, qualitative findings reveal enhanced reflective ability, communication, and teamwork, indicating changes in attitudes and behavior toward greater productivity and participation.